Experimental Performance of a Finned-tube Silica Gel Adsorption Chiller for Air-Conditioning Application - Atiya, Mohammed A.; Lattieff, Farkad A.; Al-Hemiri, Adil A. (Al-Khwarizmi Engineering Journal, 2014)
This work presents the construction of a test apparatus for air-conditioning application that is flexible in changing a scaled down adsorbent bed modules. To improve the heat and mass transfer performance of the adsorbent bed, a finned-tube of the adsorbent bed heat exchanger was used. The results show that the specific cooling power (SCP) and the coefficient of performance (COP) are 163 W/kg and 0.16, respectively, when the cycle time is 40 min, the hot water temperature is 90oC, the cooling water temperature is 30oC and the evaporative water temperature is 11.4oC.